(untitled) (Research, Society and Development, 2022)
Objective: to describe the educational strategies for the empowerment of pregnant women in the prevention of obstetric violence. Method: integrative literature review structured in six steps guided by the Preferred eporting Items for Systematic Reviews and Meta-Analyses checklist. The databases Latin American and Caribbean Literature on Health Sciences, Online System for Search and Analysis of Medical Literature, Nursing Database, INDEX Psychology and the Índice Bibliográfico Español en Ciencias de La Salud. Result: the final sample totaled eleven articles that considered the conversation circles, adherence to prenatal care, permanent education for the multiprofessional team, use of support material and use of the stork network as important approaches to carry out health education for the empowerment of pregnant women in the prevention of obstetric violence. Conclusion: educational strategies during prenatal care promote the empowerment of pregnant women by developing their autonomy in making decisions about childbirth and preventing situations of obstetric violence.